Fireproof bimetallic composite panel and preparation method thereof

By covering the aluminum plate with copper plate and adding composite filler and modified polyglycidyl methacrylate to the polymer film, the problems of flammable and poor fire resistance of the traditional aluminum-plastic plates are solved, and the high peel strength, excellent mechanical properties, and good oxidation and corrosion resistance of the bimetal composite plate are achieved.

CN119217841BActive Publication Date: 2025-04-01JIANGSU ALUMGQI NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411738794.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-01
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

The polyethylene interlayer of traditional aluminum-plastic boards is flammable, which makes it easy to cause fires under high pressure, heat release, discharge and other conditions. The fire resistance of existing aluminum composite boards is poor, the peel strength between the core material and the aluminum alloy is not high, the service life is short, and the oxidation resistance and corrosion resistance are poor.

Method used

A bimetallic composite plate with copper plates covered with polymer film on an aluminum plate is used. Composite fillers and modified polyglycidyl methacrylate are added to the polymer film to improve peel strength and mechanical properties, enhance oxidation and corrosion resistance, and improve flame retardant performance and fire resistance.

Benefits of technology

It has achieved improvements in the peel strength and mechanical properties of polymer films, enhanced oxidation and corrosion resistance, improved flame retardant performance and fire resistance, and extended the service life of bimetal composite panels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of bimetallic composite plates, and discloses a fireproof bimetallic composite plate and a preparation method thereof. The preparation method comprises the following steps: selecting an aluminum plate as a base layer, covering a polymer film on the upper surface of the aluminum plate to form an adhesive layer, covering a copper plate on the upper surface of the adhesive layer, and compounding the fireproof bimetallic composite plate under a temperature condition of 150-200 DEG C; the polymer film comprises: ethylene-vinyl acetate copolymer, epoxy resin, polymethyl methacrylate, modified poly(methyl methacrylate glycidyl ester), composite filler, and polyamide; the bimetallic composite plate prepared by the invention is prepared by covering the copper plate on the aluminum plate through the polymer film, the polymer film is added with composite filler and modified poly(methyl methacrylate glycidyl ester), the peel strength and mechanical properties of the polymer film are improved, the anti-oxidation and corrosion resistance are good, and the flame retardant property and fireproof grade are high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bimetallic composite plates, and in particular relates to a fireproof bimetallic composite plate and a preparation method thereof. Background Art

[0002] With the acceleration of industrialization, large buildings in cities are gradually increasing. The fire protection difficulties faced by large buildings are greater than those of ordinary buildings. The country has put forward higher and higher requirements on the fire resistance of materials used in high-rise buildings. The polyethylene interlayer of traditional aluminum-plastic panels itself has many defects, such as: flammable materials, which are very easy to cause fires under conditions of high pressure, heat release, and discharge.

[0003] Fireproof aluminum composite panels are a new type of non-combustible product, with aluminum alloy as the surface and natural inorganic material as the core material. The panel structure is bonded with special polymer film and cured by heating. Advanced technology is used to achieve perfect combination and improve the mechanical properties of the panel, thus forming a new generation of indoor and outdoor decorative materials with fashionable appearance, superior performance and convenient construction. However, aluminum composite panels often rely on surface coating paint to gain color, poor fire resistance, and low peeling strength between the core material and aluminum alloy, resulting in a short service life and poor anti-oxidation and corrosion resistance.

[0004] The performance of existing single-component metal materials can no longer meet the needs of the rapid development of modern industry. As an alternative product, bimetallic composite panels not only have the advantages of both metals, but also greatly reduce the use of rare metals, reduce production costs, and have a very high cost-effectiveness. The fire resistance of metal composite panels in practical applications is highly valued, and the polymer film used for bonding is also an important indicator for determining fire resistance. When used for building curtain walls and interior and exterior wall decoration, the performance will be significantly reduced after long-term aging in the natural environment, resulting in the metal panel easily separating from the polymer film, which reduces the service life of the metal composite panel. Summary of the invention

[0005] In order to solve the deficiencies mentioned in the above-mentioned background technology, the purpose of the present invention is to provide a fireproof bimetallic composite plate and a preparation method thereof. The bimetallic composite plate is prepared by covering an aluminum plate with a copper plate through a polymer film. The polymer film is added with composite fillers and modified poly(glycidyl methacrylate), which improves the peel strength and mechanical properties of the polymer film, has good antioxidant and corrosion resistance, and has high flame retardant properties and fire resistance grade.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] A method for preparing a fireproof bimetallic composite plate comprises the following steps: selecting an aluminum plate as a base layer, covering the upper surface of the aluminum plate with a polymer film to form an adhesive layer, covering the upper surface of the adhesive layer with a copper plate, and compounding the copper plate under a temperature condition of 150-200°C to form a fireproof bimetallic composite plate;

[0008] The polymer film comprises the following raw materials in parts by weight: 50-70 parts of ethylene-vinyl acetate copolymer, 10-20 parts of epoxy resin, 10-15 parts of polymethyl methacrylate, 5-10 parts of modified polyglycidyl methacrylate, 2-5 parts of composite filler, and 1-3 parts of polyamide;

[0009] The composite filler is prepared by grafting a synthetic flame retardant with silicon dioxide and carbon nanotubes by chemical reaction; and the modified poly(glycidyl methacrylate) is prepared by coating graphene oxide on the surface of poly(glycidyl methacrylate) by chemical reaction.

[0010] Preferably, the method for preparing the polymer film comprises the following steps: weighing each raw material by weight, mixing ethylene-vinyl acetate copolymer, epoxy resin, polymethyl methacrylate, composite filler, modified polyglycidyl methacrylate and polyamide, granulating the mixture with a screw granulator, and then extruding the mixture with a screw extruder and calendering the mixture with a calender to prepare the polymer film.

[0011] Preferably, the method for preparing the composite filler comprises the following steps:

[0012] A. 1,5-naphthalenediamine and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane are placed in a reactor, ethanol solvent is added, and ultrasonic dispersion is performed uniformly. After terephthalaldehyde is dissolved in ethanol, the mixture is added into the reactor and stirred and mixed. The mixture is refluxed at 55-70°C for 4-6 hours. After DOPO is dissolved in ethanol, the mixture is added into the reactor, and the mixture is continued to react at 75-90°C for 5-6 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, washed, and dried to obtain a DOPO derivative.

[0013] B. Take carbon nanotubes in a mixed solution of concentrated sulfuric acid and concentrated nitric acid, place it at 70-85°C for reaction for 4-6 hours, filter and wash the product until it is neutral and dry it, place the obtained oxidized carbon nanotubes in a reactor, add thionyl chloride and N,N-dimethylformamide, ultrasonically disperse for 1-2 hours, then place it at 70-85°C for reflux reaction for 20-24 hours, and after the reaction is completed, rotary evaporate and dry it to prepare chlorinated carbon nanotubes;

[0014] C. Nano-silica and acyl chloride carbon nanotubes are ultrasonically dispersed in N,N-dimethylformamide, DOPO derivatives and pyridine are added and mixed evenly, and the mixture is refluxed at 70-80° C. for 18-24 hours to prepare a composite filler.

[0015] Preferably, in step A, the molar ratio of 1,5-naphthalenediamine, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, terephthalaldehyde and DOPO is 0.33-0.4: 0.65-0.72: 1: 1.4-2.

[0016] Preferably, the preparation method of the modified polyglycidyl methacrylate comprises the following steps:

[0017] (1) Polyvinyl pyrrolidone was stirred and dissolved in anhydrous ethanol, and stirred for 25-40 minutes under nitrogen. Then glycidyl methacrylate was added, and the temperature was raised to 65-75°C. Azobisisobutyronitrile was added and reacted for 7-9 hours. After the reaction was completed, the poly(glycidyl methacrylate) was obtained by washing and drying.

[0018] (2) ultrasonically dispersing graphene oxide in deionized water to obtain a dispersion, dissolving p-phenylenediamine in deionized water and adding it to the dispersion, ultrasonically mixing and reacting at 30-50° C. for 18-24 hours. After the reaction is completed, filtering, washing and drying to obtain amino-modified graphene oxide;

[0019] (3) Poly(glycidyl methacrylate) and amino-modified graphene oxide are placed in a reactor, deionized water is added for ultrasonic dispersion, and the mixture is reacted at 40 to 50° C. for 18 to 24 hours. After the reaction is completed, the mixture is washed and dried to obtain modified poly(glycidyl methacrylate).

[0020] Preferably, in step (1), the mass ratio of polyvinyl pyrrolidone to glycidyl methacrylate is 1:3.2-3.5.

[0021] Preferably, in step (3), the mass ratio of poly(glycidyl methacrylate) to amino-treated graphite oxide is 1:1.8-2.1.

[0022] A fireproof bimetal composite panel is made by the preparation method as described above.

[0023] Beneficial effects of the present invention:

[0024] The invention uses 1,5-naphthalenediamine, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and terephthalaldehyde as raw materials to prepare a flame retardant DOPO derivative, then condenses the silanol group at one end of the DOPO derivative with the hydroxyl group on the surface of nano-silicon dioxide, and reacts the amino group at the other end of the DOPO derivative with the acyl chloride group on the surface of acyl chloride carbon nanotube, so as to graft silicon dioxide and carbon nanotube together with the DOPO derivative as a connector. The carbon nanotube has an extremely high specific surface area, an excellent elastic modulus, excellent thermal properties and an extremely low thermal expansion coefficient. Due to the connection and restriction of the DOPO derivative, the carbon nanotube is tightly combined with the nano-silicon dioxide, and the dispersion of the nano-silicon dioxide and the carbon nanotube is further promoted, so as to avoid the decrease of the bonding strength of the polymer film due to the agglomeration of the nano-silicon dioxide and the carbon nanotube, and the carbon nanotube is combined with the nano-silicon dioxide to improve the heat resistance and mechanical properties of the polymer film.

[0025] The invention prepares poly(glycidyl methacrylate) by free radical polymerization reaction, and at the same time, the invention uses the amino group at one end of the antioxidant p-phenylenediamine to undergo grafting reaction with the epoxy group in the graphene oxide structure to prepare the amination graphene oxide, and then uses a chemical reaction to cause the amino group in the amination graphene oxide structure to undergo ring-opening reaction with the epoxy group on the surface of the poly(glycidyl methacrylate) to obtain the graphene oxide-coated modified poly(glycidyl methacrylate), wherein the graphene oxide has excellent mechanical properties and is impermeable to oxygen and water. Taking advantage of the properties of high specific surface area, graphene oxide is coated on the surface of poly(glycidyl methacrylate), which increases the interlayer spacing of graphene oxide, is beneficial to the dispersion of graphene oxide, and at the same time increases the contact area between graphene oxide and the matrix, improves the compatibility of the material and the matrix, and epoxy resin and modified poly(glycidyl methacrylate) can be co-cured with the curing agent polyamide to form two cross-linked networks, which enhance the density of the polymer film, strengthen the bonding ability with the metal sheet, increase the peel strength, and at the same time improve the anti-corrosion effect and mechanical properties of the polymer film.

[0026] The polymer film prepared by the present invention has excellent flame retardancy, is safer and more reliable, and the copper plate and the aluminum plate are bonded and fixed by the polymer film, with a larger bonding area and better bonding effect, and the polymer adhesive film has the advantages of high peel strength, resistance to heat and oxygen aging, and strong compressive resistance. In addition, the bimetallic composite plate prepared by the present invention is a composite plate in which a copper plate is coated on an aluminum plate through a polymer film, so as to achieve the effect of saving resources and reducing costs without changing the appearance effect. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Embodiment 1 A method for preparing a composite filler comprises the following steps:

[0029] A. Take 5.28g of 1,5-naphthalenediamine and 14.46g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane in a reactor, add 50mL of ethanol solvent, and disperse evenly by ultrasonication. Take 13.41g of terephthalaldehyde, dissolve it in 50mL of ethanol, add it to the reactor, stir and mix, place it under reflux at 65°C for 6h, then take 34.59g of DOPO, dissolve it in 100mL of ethanol, add it to the reactor, place it under 85°C for 6h, and cool it to room temperature after the reaction is completed. After filtering, washing and drying, a DOPO derivative is prepared;

[0030] B. Take 2g of carbon nanotubes in a mixture of 87mL of concentrated sulfuric acid and 29mL of concentrated nitric acid, place it at 80°C for reaction for 5h, filter and wash the product until it is neutral and dry it, take 0.4g of the obtained oxidized carbon nanotubes and place it in a reactor, add 100mL of dichlorothionyl and 2mL of N,N-dimethylformamide, ultrasonically disperse it for 1h, then place it at 80°C for reflux reaction for 24h, and after the reaction is completed, rotary evaporate and dry it to prepare chlorinated carbon nanotubes;

[0031] C. Take 0.1g of nano-silica and 0.4g of acyl chloride carbon nanotubes and ultrasonically disperse them in 100mL of N,N-dimethylformamide, add 0.8g of DOPO derivative and 0.15mL of pyridine and mix them evenly, place them under reflux at 80°C for 24h to prepare a composite filler.

[0032] Example 2 A method for preparing modified polyglycidyl methacrylate comprises the following steps:

[0033] (1) 3.2 g of polyvinyl pyrrolidone was dissolved in 200 mL of anhydrous ethanol by stirring, and stirred for 30 min under nitrogen. Then 10.3 g of glycidyl methacrylate was added, and the temperature was raised to 70°C. 0.15 g of azobisisobutyronitrile was added and reacted for 8 h. After the reaction was completed, the mixture was washed and dried to obtain polyglycidyl methacrylate.

[0034] (2) 1 g of graphene oxide was ultrasonically dispersed in 100 mL of deionized water to obtain a dispersion, 1.7 g of p-phenylenediamine was dissolved in 100 mL of deionized water and added to the dispersion, ultrasonically mixed and reacted at 50° C. for 20 h. After the reaction was completed, the mixture was filtered, washed and dried to obtain amino-modified graphene oxide;

[0035] (3) Take 1 g of poly(glycidyl methacrylate) and 2 g of amino-modified graphene oxide into a reactor, add 200 mL of deionized water for ultrasonic dispersion, and place it at 45 °C for reaction for 24 h. After the reaction is completed, it is washed and dried to prepare modified poly(glycidyl methacrylate).

[0036] Example 3 A polymer film includes the following raw materials in parts by weight: 52 parts of ethylene-vinyl acetate copolymer, 10 parts of epoxy resin, 10 parts of polymethyl methacrylate, 5 parts of modified polyglycidyl methacrylate prepared in Example 2, 2 parts of the composite filler prepared in Example 1, and 1 part of polyamide.

[0037] The preparation method of the polymer film comprises the following steps: weighing each raw material by weight, mixing ethylene-vinyl acetate copolymer, epoxy resin, polymethyl methacrylate, composite filler, modified poly(glycidyl methacrylate) and polyamide, granulating the mixture with a screw granulator, and then extruding the mixture with a screw extruder and calendering the mixture with a calender to prepare a polymer film.

[0038] A method for preparing a fireproof bimetallic composite plate comprises the following steps: selecting an aluminum plate as a base layer, covering the upper surface of the aluminum plate with a polymer film to form an adhesive layer, covering the upper surface of the adhesive layer with a copper plate, and applying a pressure of 0.5 MPa using a press at a temperature of 150°C to prepare the plate.

[0039] Example 4 A polymer film includes the following raw materials in parts by weight: 63 parts of ethylene-vinyl acetate copolymer, 15 parts of epoxy resin, 12 parts of polymethyl methacrylate, 7 parts of modified polyglycidyl methacrylate prepared in Example 2, 4 parts of the composite filler prepared in Example 1, and 2 parts of polyamide.

[0040] The preparation method of the above polymer film is the same as that of Example 3.

[0041] A method for preparing a fireproof bimetallic composite plate comprises the following steps: selecting an aluminum plate as a base layer, covering the upper surface of the aluminum plate with a polymer film to form an adhesive layer, covering the upper surface of the adhesive layer with a copper plate, and applying a pressure of 0.6 MPa using a press at a temperature of 180°C to form the plate.

[0042] Example 5 A polymer film includes the following raw materials in parts by weight: 70 parts of ethylene-vinyl acetate copolymer, 18 parts of epoxy resin, 15 parts of polymethyl methacrylate, 10 parts of modified polyglycidyl methacrylate prepared in Example 2, 5 parts of the composite filler prepared in Example 1, and 3 parts of polyamide.

[0043] The preparation method of the above polymer film is the same as that of Example 3.

[0044] A method for preparing a fireproof bimetallic composite plate comprises the following steps: selecting an aluminum plate as a base layer, covering the upper surface of the aluminum plate with a polymer film to form an adhesive layer, covering the upper surface of the adhesive layer with a copper plate, and applying a pressure of 0.8 MPa using a press at a temperature of 200°C to prepare the plate.

[0045] Comparative Example 1 A polymer film includes the following raw materials in parts by weight: 70 parts of ethylene-vinyl acetate copolymer, 18 parts of epoxy resin, 15 parts of polymethyl methacrylate, 10 parts of modified polyglycidyl methacrylate prepared in Example 2, 1 part of nano-silica, 4 parts of carbon nanotubes, and 3 parts of polyamide.

[0046] The preparation method of the above polymer film is the same as that of Example 3.

[0047] A method for preparing a fireproof bimetallic composite panel is the same as that in Example 5.

[0048] Comparative Example 2 A polymer film includes the following raw materials in parts by weight: 70 parts of ethylene-vinyl acetate copolymer, 18 parts of epoxy resin, 15 parts of polymethyl methacrylate, 10 parts of polyglycidyl methacrylate prepared in Example 2, 5 parts of the composite filler prepared in Example 1, and 3 parts of polyamide.

[0049] The preparation method of the above polymer film is the same as that of Example 3.

[0050] A method for preparing a fireproof bimetallic composite panel is the same as that in Example 5.

[0051] Performance Testing

[0052] The polymer films and fireproof bimetallic composite panels prepared in Examples 3-5 and Comparative Examples 1-2 were subjected to performance tests: the tensile shear strength was measured according to GB / T 7124-2008, with a loading speed of 5 mm / min; the peel strength was measured according to GB / T 7122-1996, and the peel strength after heat aging at 90°C / 504h was measured, with a loading speed of 30 mm / min; the salt spray aging was tested according to GJB150.11A, the test chamber temperature was adjusted to 35°C before the test, and the specimen was kept under this condition for at least 2h before spraying, and the salt spray was sprayed for 48h. During this period, the salt spray sedimentation rate and the pH value of the sedimentation solution were measured at least every 24h to ensure that the sedimentation rate of the salt solution was 1~3mL / (80cm2 ·h), dried for 48h, and the test piece was taken out after 480h of salt spray test, and the performance test was carried out after being placed under standard conditions for 24h; the limiting oxygen index of the polymer film was determined according to GB / T 2406.2-2009; the flexural strength of the bimetallic composite plate was determined according to JCT 2561-2020; the combustion performance grade of the bimetallic composite plate was determined according to GB8624-2012, and the data results are shown in Table 1.

[0053] Table 1 Test results of sample performance

[0054]

[0055] From the data results in Table 1, it can be seen that the materials prepared in Examples 3-5 of the present invention have high shear strength and peel strength, and the peel strength does not decrease significantly after heat aging and salt spray aging, and at the same time have excellent tensile strength and flexural strength, and high flame retardancy and fire resistance. Among them, in Comparative Example 1, nano-silicon dioxide and carbon nanotubes are simply blended, and the shear strength, peel strength, mechanical properties, flame retardancy and fire resistance of the materials are lower than those of Examples 3-5. In Comparative Example 2, poly(glycidyl methacrylate) is not modified, and the peel strength of the materials after heat aging and salt spray aging is significantly reduced, and the tensile strength and flexural strength are slightly worse than those of Examples 3-5.

[0056] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0057] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of the present invention to be protected.

Claims

1. A method for preparing a fireproof bimetallic composite panel, characterized in that: The following steps are involved: An aluminum plate is selected as the base layer, a polymer film is coated on the surface of the aluminum plate to form an adhesive layer, a copper plate is coated on the adhesive layer, and the composite is made into a fireproof bimetallic composite plate at a temperature of 150-200°C; The polymer film comprises the following raw materials in parts by weight: 50-70 parts of ethylene-vinyl acetate copolymer, 10-20 parts of epoxy resin, 10-15 parts of polymethyl methacrylate, 5-10 parts of modified polyglycidyl methacrylate, 2-5 parts of composite filler, and 1-3 parts of polyamide; The composite filler is made by grafting a synthetic flame retardant with silicon dioxide and carbon nanotubes by chemical reaction; the modified poly(glycidyl methacrylate) is made by coating graphene oxide on the surface of poly(glycidyl methacrylate) by chemical reaction; The preparation method of the composite filler comprises the following steps: A. 1,5-naphthalenediamine and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane are placed in a reactor, ethanol solvent is added, and ultrasonic dispersion is performed uniformly. After terephthalaldehyde is dissolved in ethanol, the mixture is added into the reactor and stirred and mixed. The mixture is refluxed at 55-70°C for 4-6 hours. After DOPO is dissolved in ethanol, the mixture is added into the reactor, and the mixture is continued to react at 75-90°C for 5-6 hours. After the reaction is completed, the mixture is cooled to room temperature, filtered, washed, and dried to obtain a DOPO derivative. B. Take carbon nanotubes in a mixed solution of concentrated sulfuric acid and concentrated nitric acid, place it at 70-85°C for reaction for 4-6 hours, filter and wash the product until it is neutral and dry it, place the obtained oxidized carbon nanotubes in a reactor, add thionyl chloride and N,N-dimethylformamide, ultrasonically disperse for 1-2 hours, then place it at 70-85°C for reflux reaction for 20-24 hours, and after the reaction is completed, rotary evaporate and dry it to prepare chlorinated carbon nanotubes; C. Nano-silicon dioxide and acyl chloride carbon nanotubes are ultrasonically dispersed in N,N-dimethylformamide, DOPO derivatives and pyridine are added and mixed evenly, and the mixture is refluxed at 70-80° C. for 18-24 hours to prepare a composite filler; The preparation method of the modified polyglycidyl methacrylate comprises the following steps: (1) Polyvinyl pyrrolidone was stirred and dissolved in anhydrous ethanol, and stirred for 25-40 minutes under nitrogen. Then glycidyl methacrylate was added, and the temperature was raised to 65-75°C. Azobisisobutyronitrile was added and reacted for 7-9 hours. After the reaction was completed, the poly(glycidyl methacrylate) was obtained by washing and drying. (2) ultrasonically dispersing graphene oxide in deionized water to obtain a dispersion, dissolving p-phenylenediamine in deionized water and adding it to the dispersion, ultrasonically mixing and reacting at 30-50° C. for 18-24 hours. After the reaction is completed, filtering, washing and drying to obtain amino-modified graphene oxide; (3) Poly(glycidyl methacrylate) and amino-modified graphene oxide are placed in a reactor, deionized water is added for ultrasonic dispersion, and the mixture is reacted at 40 to 50° C. for 18 to 24 hours. After the reaction is completed, the mixture is washed and dried to obtain modified poly(glycidyl methacrylate).

2. The method for preparing a fireproof bimetallic composite panel according to claim 1, characterized in that: The preparation method of the polymer film comprises the following steps: weighing each raw material by weight, mixing ethylene-vinyl acetate copolymer, epoxy resin, polymethyl methacrylate, composite filler, modified polyglycidyl methacrylate and polyamide, granulating the mixture with a screw granulator, and then extruding the mixture with a screw extruder and calendering the mixture with a calender to prepare the polymer film.

3. The method for preparing a fireproof bimetallic composite panel according to claim 1, characterized in that: In the step A, the molar ratio of 1,5-naphthalenediamine, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, terephthalaldehyde and DOPO is 0.33-0.4: 0.65-0.72: 1: 1.4-2.

4. The method for preparing a fireproof bimetallic composite panel according to claim 1, characterized in that: In the step (1), the mass ratio of polyvinyl pyrrolidone to glycidyl methacrylate is 1:3.2-3.

5.

5. The method for preparing a fireproof bimetallic composite panel according to claim 1, characterized in that: In the step (3), the mass ratio of poly(glycidyl methacrylate) to amino-treated graphite oxide is 1:1.8-2.

1.

6. A fireproof bimetallic composite panel, characterized in that: Prepared by the preparation method described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Copper-plastic composite board process technique and copper-plastic composite board

    CN101254678A

  • Preparation method for positive electrode catalyst of fuel cell

    CN105845952A

Cited By

  • Fireproof composite aluminum plate strip and preparation method thereof

    CN121536051A

  • Fireproof composite aluminum plate strip and preparation method thereof

    CN121536051B